2012
DOI: 10.1002/path.3956
|View full text |Cite
|
Sign up to set email alerts
|

15‐Hydroxyprostaglandin dehydrogenase associates with poor prognosis in breast cancer, induces epithelial–mesenchymal transition, and promotes cell migration in cultured breast cancer cells

Abstract: Breast cancer is the most frequent cancer and the leading cause of cancer-related deaths in women worldwide. The prognosis of breast cancer is tightly correlated with the degree of spread beyond the primary tumour. Arachidonic acid (AA) and prostaglandin E(2) (PGE(2)) are known to regulate tumour metastasis enabling epithelial-mesenchymal transition (EMT). However, the detailed role of 15-hydroxyprostaglandin dehydrogenase (HPGD), the key enzyme degrading prostaglandin E(2) , remains unclear in breast cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Its presence at higher levels in ERÀ cases suggests other roles in normal breast tissue. The HPGD gene encoding an alcohol dehydrogenase regulated by progesterone is a poor prognostic marker in breast cancer (47), and is overexpressed in ERÀ cell lines and ERÀ tumors (48). The specific roles and interaction of these genes in the genesis of ERÀ tumors clearly needs further work, but just as clearly, point to a heretofore unsuspected role of lipid metabolism abnormalities in the genesis of ERÀ breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Its presence at higher levels in ERÀ cases suggests other roles in normal breast tissue. The HPGD gene encoding an alcohol dehydrogenase regulated by progesterone is a poor prognostic marker in breast cancer (47), and is overexpressed in ERÀ cell lines and ERÀ tumors (48). The specific roles and interaction of these genes in the genesis of ERÀ tumors clearly needs further work, but just as clearly, point to a heretofore unsuspected role of lipid metabolism abnormalities in the genesis of ERÀ breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the authors have shown that the key enzyme degrading PGE2, 15-hydroxyprostaglandin dehydrogenase, has a dual role in breast cancer. On the one hand previous studies have indicated HPGD as a tumor-suppressor gene and downregulated in cancer as compared with normal tissues [66], but on the other hand it is highly upregulated in those breast cancer patients with poor outcome [67].…”
Section: Role Of Eicosanoids In Breast Cancermentioning
confidence: 95%
“…A breast cancer tissue microarray (TMA, see ref. 18) and a sector of a lung cancer TMA (19) were used for the Grp78 analysis. One-hundred and eighty-two primary breast and 36 primary lung tumors became eligible for evaluation.…”
Section: Grp78 Tissue Microarraysmentioning
confidence: 99%